Identifying factors that shape whether digital food marketing appeals to children - Camilo E Valderrama; Dana Lee Olstad; Yun Yun Lee; Joon Lee (Cambridge University Press, 2023)
Abstract Objective: Children are frequently exposed to unhealthy food marketing on digital media. This marketing contains features that often appeal to children, such as cartoons or bold colours. Additional factors can also shape whether marketing appeals to children. In this study, in order to assess the most important predictors of child appeal in digital food marketing, we used machine learning to examine how marketing techniques and children's socio-demographic characteristics, weight, height, BMI, frequency of screen use and dietary intake influence whether marketing instances appeal to children. Design: We conducted a pilot study with thirty-nine children. Children were divided into thirteen groups, in which they evaluated whether food marketing instances appealed to them. Children's agreement was measured using Fleiss' kappa and the S score. Text, labels, objects and logos extracted from the ads were combined with children's variables to build four machine-learning models to identify the most important predictors of child appeal. Setting: Households in Calgary, Alberta, Canada. Participants: 39 children aged 6-12 years. Results: Agreement between children was low. The models indicated that the most important predictors of child appeal were the text and logos embedded in the food marketing instances. Other important predictors included children's consumption of vegetables and soda, sex and weekly hours of television. Conclusions: Text and logos embedded in the food marketing instances were the most important predictors of child appeal. The low agreement among children shows that the extent to which different marketing strategies appeal to children varies.